Kolaborasi, Kreatifitas Dan Kemanusiaan: Aktivitas Dakwah Habib Jafar Di Youtube - Yusuf Afandi (LP2M Universitas Islam Ahmad Dahlan Sinjai, 2023)
This article aims to analyze Habib Jafar al-Hadhar's da'wah activities on Youtube. The data related to this research was collected through the author's observation through the youtube accounts @jedanulis, @pemudatersesat, and @deddycobuzier as well as some comments from the audience of these accounts and supported by articles related to the theme of this research. This article highlights the implementation of his activities on YouTube and his oral and visual expressions in his da'wah. The main ways of Habib Jafar's da'wah are by prioritizing the themes of love, peace, and tolerance, using language favored by the younger generation, collaborating with YouTubers who are popular among young people, and using easy-to-understand da'wah materials. Based on these findings, this article concludes that Habib Jafar al Hadir's da'wah efforts can attract the attention of millennials who often access YouTube, thus increasing the possibility that da'wah collaboration can be well received.